Postantibiotic effect of clarithromycin alone and combined with ethambutol against Mycobacterium avium complex. - Ellis, L C (1995)
The postantibiotic effect (PAE) of clarithromycin alone and in combination with ethambutol was determined for two clinical blood isolates of Mycobacterium avium complex. An average PAE, ranging from 5.5 to 18.0 h, was noted for each isolate at each clarithromycin concentration except when isolate B was exposed to clarithromycin at the MIC. The addition of ethambutol did not enhance the PAE observed with clarithromycin alone. The clinical implications of the PAE of clarithromycin for M. avium complex remain to be determined.